2018
DOI: 10.1111/hsc.12569
|View full text |Cite
|
Sign up to set email alerts
|

The symbolic representation of community in social isolation and loneliness among older people: Insights for intervention from a rural Irish case study

Abstract: Social isolation and loneliness are common experiences of ageing in rural communities. Policy responses and interventions for social isolation and loneliness in later life are shaped by sociocultural understandings of place, relationships and social interaction. This study examined how representations of rural community in Ireland influenced the focus, relationships and activities within a befriending intervention designed to tackle social isolation and loneliness. Through a qualitative case study conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 31 publications
(44 reference statements)
0
26
0
Order By: Relevance
“…The present study therefore sheds new light on the needs of older adults in rural RCMs, including variations in priority needs from a general as well as speci c perspectives of older adults with disabilities or those living in rural areas. Since a good understanding of normative conditions may help developers of interventions to better engage older adults who do not conform to the dominant perception of community vision and functioning [24], these distinctions could foster successful implementation of social initiatives with older adults. A good understanding of community functioning is required to shape context-sensitive interventions to counter, for example, social isolation in later life.…”
Section: Discussionmentioning
confidence: 99%
“…The present study therefore sheds new light on the needs of older adults in rural RCMs, including variations in priority needs from a general as well as speci c perspectives of older adults with disabilities or those living in rural areas. Since a good understanding of normative conditions may help developers of interventions to better engage older adults who do not conform to the dominant perception of community vision and functioning [24], these distinctions could foster successful implementation of social initiatives with older adults. A good understanding of community functioning is required to shape context-sensitive interventions to counter, for example, social isolation in later life.…”
Section: Discussionmentioning
confidence: 99%
“…In situations of poor health, we found that proximal environments, especially relationships with neighbours, became increasingly important for opportunities for daily experiences of connection (Yen et al ., 2012; Michael and Yen, 2014). Nevertheless, due to increasing rents and job-market precariousness, neighbourhoods (especially in our large metropolitan field site) were felt to be transitory and no longer offer the often-idealised form of social support, such as positive neighbouring, that our participants desired (Scharf and de Jong Gierveld, 2008; Stanley et al ., 2010; Bantry-White et al ., 2018). This, along with widespread concerns about broader structural factors such as the level of the pension and inability to afford accommodation acceptable for socialising, highlights how both micro- and macro-economic considerations inhibited participants’ ability to connect (Ibrahim et al ., 2013) and at worst exclude people from having a public life altogether (Weldrick and Grenier, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The present study therefore sheds new light on the needs of older adults in rural RCMs, including variations in priority needs from a general as well as specific perspectives of older adults with disabilities or those living in rural areas. Since a good understanding of normative conditions may help developers of interventions to better engage older adults who do not conform to the dominant perception of community vision and functioning [ 25 ], these distinctions could foster successful implementation of social initiatives with older adults. A good understanding of community functioning is required to shape context-sensitive interventions to counter, for example, social isolation in later life.…”
Section: Discussionmentioning
confidence: 99%